A tributação por meio das contribuições previdenciárias sob o enfoque da semiótica - Fornazari, Marjory (2010)
The present approach, based in a theory of language as constituted of the reality and the law as a text, achieves a semiotic and dialogic analysis of the rules related to the tax by the contribution for the social insurance; that is, analyses them under the three language s degrees syntactic, semantics and pragmatics and try to offer a theoric model of validity, legality and efficacy inside the Brazilian law system in order to accomplish a more strict control in the institution, inspection, tax revenue and management in the product of the tax revenue of the contribution for the social insurance